2018
DOI: 10.1103/physrevlett.120.120502
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Communication with the Assistance of Indefinite Causal Order

Abstract: In quantum Shannon theory, the way information is encoded and decoded takes advantage of the laws of quantum mechanics, while the way communication channels are interlinked is assumed to be classical. In this Letter, we relax the assumption that quantum channels are combined classically, showing that a quantum communication network where quantum channels are combined in a superposition of different orders can achieve tasks that are impossible in conventional quantum Shannon theory. In particular, we show that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
320
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(341 citation statements)
references
References 26 publications
9
320
0
Order By: Relevance
“…If the Kraus operators of the channels N 1 , N 2 and N 3 are {K (1) i }, {K (2) j } and {K (3) k } respectively, then the Kraus operators W ijk of the full quantum 3-switch channel is…”
Section: Tripartite Quantum Switchmentioning
confidence: 99%
“…If the Kraus operators of the channels N 1 , N 2 and N 3 are {K (1) i }, {K (2) j } and {K (3) k } respectively, then the Kraus operators W ijk of the full quantum 3-switch channel is…”
Section: Tripartite Quantum Switchmentioning
confidence: 99%
“…Let us assume now that  1 and  2 cover the full set  , so that    È = constraints: 1 here, and that its complete positiveness is in fact irrelevant) 11 . We thus equivalently have the following characterisation:…”
Section: A2 Compatibility With Fixed Causal Ordersmentioning
confidence: 99%
“…Having transverse spatial modes as the target d.o.f. enables encoding qudits-as opposed to qubits-for investigating quantum communication with indefinite causal order in larger Hilbert space dimensions [5,8]. The benefits of using qudits for quantum information processing applications, such as improved security in quantum cryptography and higher information capacity in quantum communication, are well known [33,34].…”
Section: -3mentioning
confidence: 99%
“…Strikingly, it has been proposed that quantum physics allows for nonclassical causal structures where the order of events is indefinite [1,2]. It has been theoretically shown that such a possibility provides an advantage for computation [3], communication complexity [4,5], and other information processing tasks [6][7][8]. Furthermore, investigations of indefinite causal orders suggest a promising route towards a theory that combines general relativity and quantum mechanics [9,10].…”
mentioning
confidence: 99%